ANALISIS HUBUNGAN KAUSALITAS ANTARA TINGKAT SUKU BUNGA,TINGKAT INFLASI, DAN HARGA SAHAM DENGAN KURS RUPIAH TERHADAP DOLAR AMERIKA SERIKAT DI INDONESIA - Resti Junia Sari; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
The aim of this study is to see and analyze the relationship of causality between:1. The interest rate with IDR (Indonesian Rupiah) towards USD (United States Dollar). (2) the inflation rate with IDR towards USD (3) The stock prices with IDR towards UDS.This study was conducted by using qualitative with descriptive and associative, where the data was used secondary data in the form of time series from the year 2006, first quarter to the year 2016 first quarter that was obtained from the relevant institutions. To analyze the data, this study have used vector autoregressive (VAR) in order to see the relation between casuallity and variable.The finding has shown that the exchange rate and interest rate do not have a causal relationship rather than a unidirectional correlation, it means thatthe exchange rates ,both it is high or low, have no influence to interest rates however the interest rates will give an effect to exchange rate movements. Moreover, the exchange rates as well as the inflation do not have a causal relationship even one-way relationship, thus the changes in inflation have no effects to exchange rate movements and vice versa. While the exchange rates along with stock prices do not have a causal relation but stock prices have a one-way connection with the exchange rate. By this, the exchange rate movements do not have a relation with stock price movements but movements in stock prices have a relation to exchange rate movements.